Transient but not permanent benefit of neuronal progenitor cell therapy after traumatic brain injury: potential causes and translational consequences - Skardelly, Marco; Gaber, Khaled; Burdack, Swen; Scheidt, Franziska; Schuhmann, Martin U.; Hilbig, Heidegard; Meixensberger, Jürgen; Boltze, Johannes (Frontiers in Cellular Neuroscience, 2014)
Background: Numerous studies have reported a beneficial impact of neural progenitor cell (NPC) transplantation on functional outcome after traumatic brain injury (TBI) during short and medium follow-up periods. However, our knowledge regarding long-term functional effects is fragmentary while a direct comparison between local and systemic transplantation is missing so far. Objectives: This study investigated the long-term (12 week) impact of human fetal neuronal progenitor cell (hNPC) transplantation 24h after severe TBI in rats. Methods: Cells were either transplanted stereotactically (1x105) into the putamen or systemically (5x105) via the tail vein. Control animals received intravenous transplantation of vehicle solution. Results: An overall functional benefit was observed after systemic, but not local hNPC transplantation by area under the curve analysis (p<0.01). Surprisingly, this effect vanished during later stages after TBI with all groups exhibiting comparable functional outcomes 84 days after TBI. Investigation of cell-mediated inflammatory processes revealed increasing microglial activation and macrophage presence during these stages, which was statistically significant after systemic cell administration (p<0.05). Intracerebral hNPC transplantation slightly diminished astrogliosis in perilesional areas (p<0.01), but did not translate into a permanent functional benefit. No significant effects on angiogenesis were observed among the groups. Conclusion: Our results suggest the careful long-term assessment of cell therapies for TBI, as well as to identify potential long-term detrimental effects of such therapies before moving on to clinical trials. Moreover, immunosuppressive protocols, though widely used, should be rigorously assessed for their applicability in the respective setup.